PELATIHAN DAN SOSIALISASI KONSEP PARIWISATA BERKELANJUTAN BAGI PENGELOLA PARIWISATA KAMPUNG KAPITAN, KOTA PALEMBANG - Ros anna Sianipar; Jimmy H Situmorang; Rosdiana Pakpahan (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Sustainable tourism has become an essential approach in developing culture-based destinations, particularly in areas vulnerable to environmental degradation and cultural commodification. Kampung Kapitan in Palembang City is a cultural tourism destination with high historical value, yet it faces challenges in implementing sustainability principles. This community service activity aims to enhance the understanding and capacity of tourism managers through training, mentoring, and the dissemination of sustainable tourism concepts tailored to local needs. The methods employed include interactive socialization, participatory training, focused group discussions, and simulations of sustainability concept applications at the tourism site. The results indicate an increase in participants’ knowledge of sustainability principles, the emergence of collective community awareness to preserve local cultural identity, and an initial commitment to integrating environmental, social, cultural, and economic aspects into Kampung Kapitan’s tourism management. Moreover, the program encouraged community initiatives to strengthen tourism appeal based on historical narratives and local wisdom. Challenges encountered included limited time, participants’ diverse backgrounds, and insufficient supporting facilities. To address these issues, an adaptive educational approach and the development of practical sustainability guidelines were implemented. Thus, this program is expected to serve as a starting point for strengthening a more inclusive, participatory, and competitively sustainable governance of Kampung Kapitan tourism. Keywords: sustainable tourism, destination management, training, socialization, Kampung Kapitan